Eating restraint is associated with reduced attentional capture by signals of valuable food reward. (1st April 2021) - Watson, Poppy; Vasudevan, Ananda; Pearson, Daniel; Le Pelley, Mike E.
Abstract: Previous paradigms used to examine attentional distraction by task-irrelevant food words and food images were not suited for the investigation of involuntary and automatic attentional capture. In the current experiments we adapted a well-established visual-search paradigm (with eye tracking) to investigate involuntary attentional capture by food and drink rewards. We first used a satiety procedure to manipulate relative preference for different food and drink outcomes (potato chips and water in Experiment 1 and popcorn and chocolate Smarties in Experiment 2). Participants then performed the visual-search task where a coloured distractor signalled on each trial which of the two food and drink rewards was available for successful identification of the target. The signalled reward was cancelled, however, if any eye gaze was registered on the distractor. Participants were therefore motivated to try and control the automatic orienting of attention towards cues signalling valuable outcomes, in order to earn those outcomes. In both experiments we found that attention was more often captured by the distractor signalling the valuable (non-sated) outcome, replicating previous studies using this paradigm with monetary rewards. We also found that those scoring high on eating restraint (as measured with the Dutch Eating Behavior Questionnaire) were better at controlling reflexive orienting of attention to desirable food rewards. This paradigm offers a novel approach for understanding how reflexive attention and control relate to conflicts in everyday life around distracting food cues, and the moderating role of dietary restraint.